Case Study of Quebec’s Law 21 from a Mexican Perspective - Flores Hernández, Elizabeth (2026)
This paper examines the concepts of state secularism and religious freedom in the Mexican legal system through a comparative law analysis of how a law such as Quebec’s Law 21, Canada—which prohibits public officials from wearing religious symbols while performing their functions—could be considered discriminatory and violative of fundamental rights in Mexico. The methodologyincludes hermeneutic legal analysis and the interpretive method, examining four variables: grammatical, teleological, axiological, and historical. A qualitative, descriptive approach is also employed to compare perspectives between Mexico and Quebec. Thereby, it was found that, within the Mexican context, state neutrality does not imply the elimination of individuals’ religious freedom, since public functionaries retain their right to practice their religion, and any imposition of secularism on their personal appearance would be a violation of their fundamental rights. Consequently, amparo proceedings in Mexico offer an effective mechanism to protect these rights from legislation resembling Law 21. It is emphasized that the secularism of the Mexican State must respect the religiousfreedom of its citizens, ensuring that people—even those serving in public office—can freely exercise their religion without discrimination or the imposition of neutrality in their personal appearance.